2020
DOI: 10.1002/ijc.33152
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognostic factors for extracranial oligometastatic breast cancer in China

Abstract: Evidence of an oligometastatic state in metastatic breast cancer (MBC) is relatively limited. The aim of our study was to investigate the clinical features and prognostic factors for extracranial oligometastatic breast cancer and to identify the best treatment approaches in this select population. Fifty postoperative inpatients diagnosed with extracranial oligometastatic breast cancer at the National Cancer Center in China between 2009 and 2014 were consecutively enrolled. Oligometastatic breast cancer was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The innovation of our study was that we also explored whether the sequence of systemic therapy and locoregional therapy could affect survival. We found that there was no significant difference between the ST to LRT group and the LRT to ST group, similar to the study of Lan et al, which noted that among patients treated with surgical resection, there was no difference in PFS between patients having resection first and those having systemic therapy first (P = 0:807) [5]. However, Cha et al argued that systemic therapy should be made after or at the same time as local therapy to control the residual Abbreviations: ST to LRT: systemic therapy followed by locoregional therapy; LRT to ST: locoregional therapy followed by systemic therapy; ST: systemic therapy.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The innovation of our study was that we also explored whether the sequence of systemic therapy and locoregional therapy could affect survival. We found that there was no significant difference between the ST to LRT group and the LRT to ST group, similar to the study of Lan et al, which noted that among patients treated with surgical resection, there was no difference in PFS between patients having resection first and those having systemic therapy first (P = 0:807) [5]. However, Cha et al argued that systemic therapy should be made after or at the same time as local therapy to control the residual Abbreviations: ST to LRT: systemic therapy followed by locoregional therapy; LRT to ST: locoregional therapy followed by systemic therapy; ST: systemic therapy.…”
supporting
confidence: 89%
“…Finally, 20 patients received systemic treatment and surgical resection, 10 patients received systemic treatment and local treatment other than resection, and 20 patients received systemic treatment alone. The median PFS was 49.6 months, 13.8 months, and 6.9 months, respectively, and the 2-year PFS rate was 65%, 30%, and 20%, respectively [ 5 ]. Concerning patients with HR-positive and HER2-negative OMBC, Cha et al found that the median PFS was significantly longer in patients with local treatment than in patients without local treatment (30.0 vs. 18.0 months, P = 0.049) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in a systematic review examining prognostic factors on survival in patients with oligometastatic breast cancer, solitary metastasis was associated with better OS 8 . In a study of 50 patients with extracranial oligometastatic breast cancer, those with single metastasis highly benefited from systemic chemotherapy and surgical resection and gained survival advantage with statistical significance 16 .…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that BC patients with OMBD do not have . Indeed, in a study of fty patients with extracranial oligometastatic breast cancer, those with single metastasis were highly bene ted from systemic chemotherapy and surgical resection and gained survival advantage with statistical signi cance [17].…”
Section: Discussionmentioning
confidence: 99%